Training responsiveness of cardiorespiratory fitness and arterial stiffness following moderate‐intensity continuous training and high‐intensity interval training in adults with intellectual and developmental disabilities. Issue 12 (28th October 2021) - Melo, X.; Pinto, R.; Angarten, V.; Coimbra, M.; Correia, D.; Roque, M.; Reis, J.; Santos, V.; Fernhall, B.; Santa‐Clara, H.
Abstract: Background: Cardiorespiratory fitness (CRF) prompts antiatherogenic adaptations in vascular function and structure. However, there is an extraordinary interindividual variability in response to a standard dose of exercise, wherein a substantial number of adults with intellectual and developmental disabilities (IDD) do not improve CRF. We (1) evaluated the effects of 12‐month of moderate‐intensity continuous training (MICT) on CRF and arterial stiffness and (2) tested whether an additional 3‐month of high‐intensity interval training (HIIT) would add to improvements in CRF responsiveness and arterial stiffness. Methods: Fifteen adults with mild‐to‐moderate IDD (male adults = 9, 30.1 ± 7.5 years old) met 3 days per week for 30 min MICT for 12 months, after which the incidence of CRF responsiveness was calculated (≥5.0% change in absolute peak VO2 ). Thereafter, responders and non‐responders started HIIT for 3 months with identical daily training load/frequency. Peak VO2, local and regional indices of arterial stiffness were assessed prior to and after each period. Results: Sixty per cent of the participants were non‐responders following MICT, but the incidence dropped to 20% following HIIT ( P  = 0.03). Absolute peak VO2 values reached significant difference from pre‐intervention (+0.38 ± 0.08 L min −1, P  = 0.001) only when HIIT was added. Lower limb pulse wave velocity (PWV) decreased following MICT (−0.8 ± 1.1 m s −1, P  = 0.049), whereas central PWV only decreased following HIIT (−0.8 ± 0.9 m s −1, P  = 0.013). Conclusions: Cardiorespiratory fitness responsiveness and reductions in PWV to a 12‐month MICT period in adults with IDD improved following a period of HIIT programme inducing higher metabolic stress.